The influence of roasting and baking on fatty acids composition of consumer oilseeds - Natalia Mikołajczak (Kazimierz Wielki University, 2017)
Introduction and aim: Foods rich in nutrients have a positive effect on the human body. They are beneficial both for the health and the mind of human. Good sources of essential fatty acids and other biologically active compounds are oilseeds. It is important to include them in your daily diet. They can be added to dishes or serve as a snack. Brief description of the state of knowledge: The aim of this study was to evaluate of fatty acid composition in selected consumer oilseeds: sunflower, sesame, flax after application of typical technological processes such as roasting and baking, in different temperature, power and time ranges. In the research materials (before and after modification), the fatty acid composition was determined by gas chromatography. Summary: Based on obtained results, it was found that roasting and baking have an influence on the change in the content and composition of fatty acids. The strength of influence was dependent on the parameters (e.g. type of seed, temperature, time, power), which were used in the research. The roasting in the oven caused changes in the composition of saturated and unsaturated fatty acids, both in flax and sunflower seeds. The roasting in the microwave at 900 W affected on saturated fatty acids composition in flax seeds, similarly sunflower. In the case of sesame seeds, the influence of time on the content of mono- and polyunsaturated fatty acids was noted. The baking process caused significant changes in the fatty acid composition in the seeds from the crust of bread (flax seeds, sunflower seeds).